Can complete blood count inflammatory parameters in epithelial ovarian cancer contribute to prognosis? - a survival analysis - Mehmet Ufuk Ceran; Umit Tasdemir; Eser Colak; Tayfun Güngör (BMC, 2019)
Abstract Subjective The aim of the present study was to investigate the prognostic significance of preoperative complete blood count inflammatory markers in women operated for invasive Epithelial Ovarian Cancer (EOC). Method Two hundred forty four patients that underwent operation with the diagnosis of invasive EOC between 2006 and 2014 were included in the study. The date of operation, date of recurrence and final mortality evaluations were performed for survival analysis. The sensitivity, specificity, PPV and NPV were separately calculated with ROC analysis. Survival analysis was carried out with Kaplan Meier-Log Rank Method. Results Five-years overall survival rate was 56, 9% and 5-year disease-free survival (DFS) rate was 45,5%. Advanced disease stage, moderate-poor tumor differentiation, and the presence of recurrence were determined to have significant inverse relation at mean survival and 5-year survival rates. Neutrophil/lymphocyte ratio (NLR) and Platelet lymphocyte ratio (PLR) had prognostic effect on both DFS and overall survival based upon the cut-off values determined in the study (PLR = 231, s36, NLR = 3,83). Histopathological subtypes were not found to have any prognostic value. In correlation analysis, PLR and NLR had positive correlation with each other and negative correlation with overall survival. Conclusions Inflammatory markers such as NLR and PLR have independent prognostic value for women who undergo surgery for invasive EOC.